Hak Asasi Politik Perempuan di Indonesia Dalam Perlindungan Hukum Positif dan Hukum Islam - fernando, alam subuh (State Islamic Institute of Kudus (IAIN Kudus), 2021)
Data accumulation literature is the method used in this research, in this article it will describe women’s political rights and opened up framework that always considered women marginalized. And indoctrinating the false paradigm of woman. In the presence convention ratification of the political rights of women, that means the state has an obligation to ensure and aluminate the right of woman on the political rights. CEDAW, UDHR and DUHAM states that the rights and freedoms need to be owned by everyone without discrimination. Therefore with positive legal regulations and Islamic law the state should ensure and protect of HAM, UDHR and DHAM tend to anthropocentralize the meaning of human beings as objects in its assertion, while HAM in Islamic law is more the centralized meaning Qur’an and Hadith as its object.